2017
DOI: 10.1037/stl0000083
|View full text |Cite
|
Sign up to set email alerts
|

Service-learning in abnormal psychology: Softening the implicit stigma against the mentally ill.

Abstract: Because of stigma, people with mental illnesses report feeling isolated and lonely, tend to be reluctant to discuss their conditions, and are less likely to seek treatments. Stigma reduction programs that incorporate some form of contact with stigmatized individuals have been shown to be effective in altering self-reported negative biases. The present study tested whether contact with individuals who have mental illnesses through a service-learning project incorporated into an undergraduate psychopathology cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Shifting implicit bias may require a more intentional exposure to people in poverty doing things that are counter-stereotypical. In the two studies cited earlier (Barney et al, 2017;Kogan & Schoenfeld-Tacher, 2018), in which service-learning was linked with implicit bias change, the service experiences were not of the helper-help recipient variety and therefore may have been more effective at changing the associations between the stigmatized groups and negative descriptors. In general, these kinds of exposures have been shown to at least temporarily decrease implicit bias (Banaji & Greenwald, 2013), though long-term change remains elusive.…”
Section: Results Of Hypothesis Tests Add Nuance To Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Shifting implicit bias may require a more intentional exposure to people in poverty doing things that are counter-stereotypical. In the two studies cited earlier (Barney et al, 2017;Kogan & Schoenfeld-Tacher, 2018), in which service-learning was linked with implicit bias change, the service experiences were not of the helper-help recipient variety and therefore may have been more effective at changing the associations between the stigmatized groups and negative descriptors. In general, these kinds of exposures have been shown to at least temporarily decrease implicit bias (Banaji & Greenwald, 2013), though long-term change remains elusive.…”
Section: Results Of Hypothesis Tests Add Nuance To Previous Workmentioning
confidence: 99%
“…In a recent review, Sukhera et al (2019) reported that of 15 studies using experiential learning, five showed a pre-post change in implicit bias. In the context of servicelearning, one study showed a decrease in ageist attitudes after contact with elders in a service project (Kogan & Schoenfeld-Tacher, 2018), and another showed decreases in negative associations of people with mental illness after a service project (Barney et al, 2017). These mixed results suggest that the impact of particular techniques on implicit bias needs to continue to be explored.…”
Section: Implicit Versus Explicit Attitudesmentioning
confidence: 99%
“…Results also showed both groups had a significant decrease in all types of public stigma measured, except the recovery subscale, with nearly all small effect sizes. Past studies involving mental illness stigma interventions in abnormal psychology classes have demonstrated success in reducing mental illness stigma (e.g., Barney et al, 2017; Ferrari, 2016; Strassle, 2018); thus, equivalent results between the strengths and control groups is encouraging. These findings are also consistent with previous literature.…”
Section: Discussionmentioning
confidence: 94%
“…The IAT was used to measure several different types of bias including biases related to race [38, 4043, 5254, 57], age [46, 50], mental illness [37, 45, 47, 51, 56, 58], weight [36, 49, 55], disability [42, 44], gender [48], and others [39]. The IAT was also used to measure the effectiveness of several types of educational activities including experiential learning, didactics, videos, independent-learning, social-contact and small/large group discussion.…”
Section: Resultsmentioning
confidence: 99%